IMPACT OF MARKETING DIMENSIONS IN RAISING THE COMPETITIVENESS OF BANKING MANAGEMENT - Iqbal Kumail Awad (Scholar Express Journals, 2025)
The Marketing (MA) dimensions (Market Heterogeneity (MH), Shortage Resources (SR), Unbranded Competition (UC), Inadequate Infrastructure (II)) on Banking Management (BM) in the organizational sector. This study focused on understanding the variables to achieve highly efficient production. A sample of productive organizations in the city Baghdad, in this research, which numbered (135), and (5) questionnaire forms were incorrect. The researcher obtained valid questionnaires (130). The researcher used statistical analysis to obtain results related to search on SPSS & Smart-PLS 4. In this study, the researcher reached highly efficient results and conclusions that confirm the importance of marketing executive management in developing production strategies. This study focused on important recommendations to benefit from and document the relationship between marketing executive management and production strategies.
Keywords: marketing dimensions; banking management; organization